2013
DOI: 10.7448/ias.16.1.18621
|View full text |Cite
|
Sign up to set email alerts
|

High HIV‐1 prevalence, risk behaviours, and willingness to participate in HIV vaccine trials in fishing communities on Lake Victoria, Uganda

Abstract: IntroductionHIV epidemics in sub-Saharan Africa are generalized, but high-risk subgroups exist within these epidemics. A recent study among fisher-folk communities (FFC) in Uganda showed high HIV prevalence (28.8%) and incidence (4.9/100 person-years). However, those findings may not reflect population-wide HIV rates in FFC since the study population was selected for high-risk behaviour.MethodsBetween September 2011 and March 2013, we conducted a community-based cohort study to determine the population represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 20 publications
5
93
0
Order By: Relevance
“…This was 4 times the national HIV prevalence of 5.6% [19]. Similar high HIV prevalence (20% -28%) among fishermen, have been previously reported in Kenya and Uganda [16] [20]- [22]. In comparison to other high-risk groups such as MSM, the HIV prevalence in this study was twice that observed in bisexual MSM in Mombasa, Kenya [23].…”
Section: Hiv Prevalencesupporting
confidence: 86%
“…This was 4 times the national HIV prevalence of 5.6% [19]. Similar high HIV prevalence (20% -28%) among fishermen, have been previously reported in Kenya and Uganda [16] [20]- [22]. In comparison to other high-risk groups such as MSM, the HIV prevalence in this study was twice that observed in bisexual MSM in Mombasa, Kenya [23].…”
Section: Hiv Prevalencesupporting
confidence: 86%
“…The types of questionnaires utilized with regards to WTP were mainly interviewer-administered questionnaires, found in nine studies (Asiki et al, 2013;Deschamps et al, 2013;Kiwanuka et al, 2013;Middelkoop et al, 2008;Newman et al, 2014;Olanrewaju et al, 2014;Otwombe et al, 2011;Ruzagira et al, 2009;Suhadev et al, 2009) (Table S1). Two studies utilized a self-administered questionnaire (Chariyalertsak et al, 2011;de Bruyn et al, 2008;C.…”
Section: Resultsmentioning
confidence: 99%
“…In another study in HIV discordant couples in Uganda, the 2-year follow-up was 80.2 % (Ruzagira et al, 2011) (Table S2). In a further study, the retention rate was 76.9 % overall in a general fisher-folk population in Uganda at 12 months (Kiwanuka et al, 2013) (Table S2). With regard to factors associated with retention in these African countries, higher retention was associated with being female (Middelkoop et al, 2008;Geis et al, 2011) and being of older age (Geis et al, 2011;Ruzagira et al, 2011).…”
Section: Retentionmentioning
confidence: 95%
See 2 more Smart Citations